Rainforest Fringe Festival 2018 - Siti Shahida, Kamel; Mohamad Faizuan, bin Mat (The Tribune, 2018)
Taking place from the 6th of July until the 15th of July 2018, Rainforest Fringe Festival will bring the very best of Sarawak’s music, art, craft, film, photography, food, and culture.